Determination of microplastics in the edible green-lipped mussel Perna viridis using an automated mapping technique of Raman microspectroscopy - Leung, Matthew Ming-Lok; Ho, Yuen-Wa; Maboloc, Elizaldy Acebu; Lee, Cheng-Hao; Wang, Youji; Hu, Menghong; Cheung, Siu-Gin; Fang, James Kar-Hei (Journal of hazardous materials, 2021)
Microplastics are prevalent in marine environments and seafood and thus can easily end up in human diets. This has raised serious concerns worldwide, particularly in Hong Kong where the seafood consumption per capita can be three times higher than the global average. This study focused on the green-lipped mussel Perna viridis, a popular seafood species which is subject to a high risk of contamination by microplastics due to its filter-feeding nature. P. viridis was collected from five mariculture sites in Hong Kong and assessed for its body load of microplastics using an automated Raman mapping approach. Microplastics were found in all sites, with an average of 1.60–14.7 particles per mussel per site, or 0.21–1.83 particles per g wet weight. Polypropylene, polyethylene, polystyrene and polyethylene terephthalate were detected among the microplastics, mainly as fragments or fibres in the size range of 40–1000 µm. It was estimated that through consumption of P. viridis, the population in Hong Kong could ingest up to 10,380 pieces of microplastics per person per year. These estimated rates were high compared to the values reported worldwide, suggesting the potential human health risk of microplastics in Hong Kong and adjacent areas. [Display omitted] •Automated Raman mapping approach to identify microplastics.•Abundance of microplastics in edible mussels.•High rates of estimated human ingestion of microplastics in Hong Kong.